Self-learning guide "English Grammar Guide" discipline "Language of professional training" - Dmytryk, A. Yu.; Myroshnychenko, Maria Pavlivna (ТОВ "Цифра Принт", 2022)
The study guide is intended for foreign students of the preparatory faculty, studying English under the guidance of a teacher. The material is designed for the course program of 2nd term, which corresponds to A2-B1 levels. At this level, the structure of the previously studied material, clarification and more in-depth study is taking place. It consists of 7 chapters: Asking questions, Verb+Infinitive / Gerund, Confusing words, Passive voice, Similarities (too, so, either, neither) and Phrasal verbs. Since the task of learning the language at this stage is freeing up grammatically correct oral speech, in the guide there is an extended material on the topic Confusing words. Each theme is a summary of these grammatical topics in the form of tables and comments and there is a series of exercises to practice and consolidate skills. This guide can be used by students for independent study of these topics, and as additional material to the main course of the textbook for the teacher and the students.
Keywords: guide; verb; infinitive; gerund; modal verbs; phrasal verbs